Upper and Lower weak $sβ(\star)$-continuity (European Journal of Pure and Applied Mathematics, 2023)
This paper is concerned with the concepts of upper and lower weakly sβ(⋆)-continuous multifunctions. Moreover, some characterizations of upper and lower weakly sβ(⋆)-continuous multifunctions are investigated.
Keywords: upper weakly $sβ(β)$-continuous multifunction; lower weakly $sβ(\star)$-continuous multifunction